2014
DOI: 10.1097/sap.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Promotes Accelerated and Dysregulated Adipogenesis in Hemangioma Stem Cells

Abstract: Background Infantile hemangiomas are the most common tumor of infancy, yet there are no FDA-approved therapeutics to date. Recently, the non-selective beta-adrenergic-blocker propranolol has been shown to be a safe and effective means of treating infantile hemangiomas, though its mechanism has yet to be elucidated. We have previously demonstrated that propranolol induces early and incomplete adipogenesis in stem cells derived from hemangiomas. We hypothesize that propranolol promotes dysregulated adipogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…We found that high‐dose propranolol rapidly induced HemSC apoptosis, with induction observed within 6 hours by Annexin V assay and 24 hours by caspase‐3 assay. This is in contrast to previous studies, in which it was shown that propranolol induced HemSC death by a nonapoptotic pathway [21, 23, 41]. The difference between the present study and others mostly likely resulted from the timing of the apoptosis assessment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that high‐dose propranolol rapidly induced HemSC apoptosis, with induction observed within 6 hours by Annexin V assay and 24 hours by caspase‐3 assay. This is in contrast to previous studies, in which it was shown that propranolol induced HemSC death by a nonapoptotic pathway [21, 23, 41]. The difference between the present study and others mostly likely resulted from the timing of the apoptosis assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…We have demonstrated that HemSCs in tissues express both β1AR and β2AR, but cultured HemSCs predominantly express β2AR. Propranolol has been suggested to target HemECs [17, 21, 47, 48] and hemangioma‐derived pericytes [19], and the present study and others [2123, 41] have demonstrated that propranolol also targets HemSCs. Thus, propranolol mediates its effects by targeting multiple cell types in IHs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Propranolol in vitro affects M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT hemogenic stem cells causing dysregulated adipogenesis and apoptosis. This may explain not only the early involution of lesions treated with propranolol, but also its inability to completely remove the fatty residua of hemangiomas (13) . It is still not understood whether propranolol only targets actively proliferating hemangioma endothelial cells or whether the hemangioma endothelial cells have a unique response to propranolol (52) .…”
Section: Beta Blockers Methods Of Actionmentioning
confidence: 99%
“…Involution is maximal in over 90% of IHs by age 4 years, with well over half of untreated IHs leaving residual skin changes or scars . Evidence of the pluripotency of haemangioma stem cells to become haemangioma endothelial cells or adipocytes, and of the effects of propranolol on these populations continues to refine our understanding of the mechanism of propranolol …”
Section: Conflicts Of Interestmentioning
confidence: 99%